Pollution and its containment (Thomas Telford, 1990)
This report surveys the impact of pollution on the environment and draws attention to the short and long term implications. It attempts to give recognition to the novel element in the present situation, which is that in the conflict between development and environmental protection the point of compromise has shifted in favour of the latter.